Imaging findings of intraductal tubulopapillary neoplasm (ITPN) of the pancreas: Two case reports and literature review. Issue 6 (February 2019) - Zhang, Jingjing; Ren, Shuai; Wang, Jianhua; Ye, Dandan; Zhang, Huifeng; Qiu, Wenli; Wang, Zhongqiu
Abstract: Rationale: Intraductal tubulopapillary neoplasm (ITPN) is a rare type of pancreatic epithelial neoplasm. We report 2 cases of ITPN and detail the imaging findings. Patient concerns: The 1st case was a 36-year-old woman who complained of jaundice, yellow urine and diarrhea. She accepted ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI) examination before surgery, which all revealed a mass in the pancreatic head. The 2nd case was a 62-year-old woman who was admitted to our hospital for the treatment of a pancreatic tumor. The MRI showed a mass filled the mian pancreatic duct in the head and neck. Diagnosis: The ITPN is an intraductal, grossly visible, tubule-forming epithelial neoplasm with high-grade dysplasia and ductal differentiation without overt mucin production. Interventions: The 1st patient received percutaneous transhepatic cholangial drainage procedure, endoscopic ultrasound guided fine needle aspiration, pancreatoduodenectomy, cholecystectomy, and lymphadenectomy successively. The 2nd patient received pancreaticoduodenectomy, cholecystectomy, and partial gastrectomy. Outcomes: Two months after surgery, the follow-up MRI revealed hepatic metastasis of the 1st patient. She is still alive now. The 2nd patient was lost to follow-up. Lessons: The ITPN is a rare pancreatic neoplasm and its clinical symptoms are atypical. It is difficult to make accurate diagnosis of ITPN before surgery even though various imaging modalities are used in combination. When a solid mass growing in the lumen of the pancreatic duct, ITPN should be taken into consideration.